KONTRIBUSI SALMAN AL-FARISI DAN KEBUDAYAAN PERSIA DALAM PEMIKIRAN ISLAM - Prof Madya Madya; Dr. Wan Zailan Kamaruddin bin Wan Ali; Dr. Ahmad Zuhdi bin Ismail (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
This article as the title indicates is to examine the life and background of salman alfarisi and his position in islam and especially in the world of persian people and nation within the islamic framework. the discussion we also be focusing on the nation of salman al farisi anfd their contribution to the islam and the world